DIAGNOSTIC ACCURACY OF PLAIN X-RAY LATERAL NECK IN THE DIAGNOSIS OF CERVICAL ESOPHAGEAL FOREIGN BODIES KEEPING ESOPHAGOSCOPY AS GOLD STANDARD - Malik, Sohail Ahmad; Qureshi, Ihsan Ahmad; Muhammad, Raza (Journal of Ayub Medical College Abbottabad, 2018)
Back ground: Detection of foreign body esophagus has always been a challenge for the otolaryngologists. Among different investigations available X -ray is valuable for detection of foreign bodies as it is readily available, inexpensive and easy to operate. However, this still remains to be decided that how accurate it is? Objective; To determine the diagnostic accuracy of plain X ray lateral neck in the diagnosis of foreign bodies in cervical esophagus keeping esophagoscopy as the gold standard Materials and Methods This descriptive study was conducted at the outpatient department of ENT, Ayub Medical Institute (AMI) Abbottabad, from Mar to Sep 2016. A total of 290 patients were included in this study and all the patients had X -ray lateral view of neck, followed by endoscopy (gold standard). Diagnostic accuracy of plain X - ray lateral view of neck was detected by determining sensitivity, specificity and accuracy. Results: The sensitivity, specificity and accuracy of plain X - ray lateral view of neck was 91.7%, 80%, and 89.7%, respectively. Conclusion: X - Ray lateral view of neck is a reliable investigation and should be advised among all the patients with history of foreign body ingestion